An Analysis of the Cultural Tourism Product Satisfaction Level in Kerala - Kumar, Suresh; Thanikkad, Jaseela (Atna Journal of Tourism Studies, 2023)
Cultural Tourism implies “A type of tourism activity in which the visitor’s essential motivation is to learn, discover, experience and consume the tangible and intangible cultural attractions/products in a tourism destination. Kerala, referred to as ‘God’s Own Country’, enjoys unique geographical features and its classical art forms, colourful festivals, exotic cuisine etc., are some of the cultural marvels that attract travellers. Though the share of cultural tourism in the tourism development of the state has not been assessed in quantitative terms, the arrival of foreign and domestic tourists to cultural tourism destinations in Kerala undoubtedly accentuate the contribution of cultural tourism to the state’s exchequer. The level of satisfaction that cultural products that the state tourism offers is subjected to analysis to explore the principal factors and confirm whether they are significant reflections of satisfaction from cultural products. The study asserts the need for redefining and revamping the role of cultural events, monuments such as Synagogue and religious places aimed to a provide a high level of satisfaction so as to attract cultural tourists to destinations in Kerala.